(untitled) (TAJ: Journal of Teachers Association, 2009)
The study was carried out in Medicine and Pediatrics Department of Rajshahi Medical College Hospital, and Natore Sadar Hospital, both are located in the northern territory of Bangladesh. Period of study ranged from admission of patients till discharge. On 8th June 2008, 83 patients of Singra Upazilla Natore were admitted in Rajshahi Medical College Hospital and Natore Sadar Hospital with the history of consumption of Puffer fish. A presumptive diagnosis of Puffer fish poisoning was made on the basis of classical clinical presentations followed by Puffer fish ingestion. Blood and urine samples from 38 patients were sent to Frankfurt, Germany for toxicological analysis. The cases were clinically reviewed periodically and routine investigations were done. Report of the toxicological study confirmed the diagnosis of tetrodotoxin poisoning. Important neurological symptoms observed were peri-oral paresthesia (71), tingling over entire body (50), dizziness (35), headache (20). Muscular paralysis of the limbs was noted in 13 patients, of which 7 patients developed respiratory involvement. All the patients who developed respiratory involvement died. Early diagnosis and supportive management could ensure a safe and favorable outcome. Management of respiratory failure by ventilator support can be life saving. doi: 10.3329/taj.v21i2.3790 TAJ 2008; 21(2): 121-125